HUBUNGAN ANTAR PERLAKUAN ORANGTUA DENGAN KONTROL DIRI SISWA DI SEKOLAH - Puspita, Minda; Erlamsyah, Erlamsyah; Syahniar, Syahniar (Konselor, 2013)
Families, especially parents play an important role in the life of a child. Because parents through their actions will shape the character, the attitude and actions of children. Actually many students have low self-control because of parenting. The research purpose to reveal correlation the parenting with self-control students. Research methods used are descriptive correlational. Result of research show parenting is quite good, self-control students is quite high and there is a significant correlation parenting with self-control students.